2015
DOI: 10.1680/adcr.13.00090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of curing, fibre content and exposures on compressive strength and elasticity of UHPC

Abstract: The paper presents an experimental study on the evaluation of the compressive strength and modulus of elasticity of ultra-high performance concrete (UHPC) prepared with varying steel fibre contents, cured in water and exposed in air, and subjected to three exposure conditions (after 28 d of curing): laboratory environment, alternate heatingcooling cycles (heating at 608C for 2 d and then cooling at room temperature for 2 d), and alternate wet-dry cycles (wetting for 2 d in aggressive salt solution and then dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 9 publications
2
14
0
4
Order By: Relevance
“…As seen in Figure 12, most cylinders recorded a modulus near 50 GPa regardless of curing temperature after maturities of 500°C-days, similar to values reported in literature (Ahmad and Hakeem 2015, Graybeal 2011, Howard et al 2018). Figure 13 shows that higher temperature curing conditions yielded higher fc than for colder conditions at a given maturity.…”
Section: Isothermal Curing Results -Group Asupporting
confidence: 86%
See 1 more Smart Citation
“…As seen in Figure 12, most cylinders recorded a modulus near 50 GPa regardless of curing temperature after maturities of 500°C-days, similar to values reported in literature (Ahmad and Hakeem 2015, Graybeal 2011, Howard et al 2018). Figure 13 shows that higher temperature curing conditions yielded higher fc than for colder conditions at a given maturity.…”
Section: Isothermal Curing Results -Group Asupporting
confidence: 86%
“…This cross-over effect is characterized by rapid strength gain at early ages but lower ultimate strength for high-temperature curing when compared to low-temperature curing, which results in slower but higher ultimate strength gain. Ahmad and Hakeem (2015) investigated the effects of air and water curing at 22°C on compressive strength and elastic modulus of UHPC at a variety of fiber contents after 28 days. For a fiber content of 6.2% by weight, curing in air and water resulted in compressive strengths of 149 and 163 MPa and elastic moduli of 49 and 57 GPa, respectively, indicating improved mechanical properties after water curing.…”
Section: Uhpc Mechanical Propertiesmentioning
confidence: 99%
“…This is due to the positive influence of the steel fibres on the strength of RPC. The results obtained in this study is consistent with the past studies [36,[57][58][59] which were conducted on the steel fibre incorporated in the concrete which concluded that the inclusion of steel fibres in the concrete increases the modulus of elasticity of the concrete noticeably.…”
Section: Modulus Of Elasticitysupporting
confidence: 92%
“…The improvement in the compressive strength under high temperature is due to the accelerated hydration of cementitious material and the secondary hydration between mineral admixtures and calcium hydroxide 21 . Moreover, higher curing temperature showed positive effect on the modulus of elasticity of UHPC due to enhanced hydration of cementitious materials 22 . The flexural strength of UHPFRC produced with ground granulated blast-furnace slag (GGBS) was significantly improved under higher temperature curing.…”
Section: Introductionmentioning
confidence: 96%